PENGARUH LAMA PASTEURISASI DAN LAMA PENYIMPANAN TERHADAP KUALITAS AIR SUSU SAPI PERAH FRIESIAN HOLSTEIN - Habibah Habibah (Bioscientiae, 2011)
This research executed in Technological Laboratory of Majors Agriculture Budidaya of Faculty Of Agriculture UNLAM. This Research aim to know influence long time pasteurized and old deposity to irrigate milk quality of dairy cattle Fresian Holstein. Method used by is series of experiment with Complete Random Device ( factorial RAL) Pattern ( two factor). Factor A is long time pasteurized ( A1= 10 minute, A2= 20 minute and A3 minute= 30 minute). Factor B is depository old ( B1= 0 day, B2= 3 day, B3= 6 day, B4= 9 day, and B5= 12 day). The material used in this research was 4 litre which irrigate milk of dairy cattle of result of pressing out tidy morning in sterile bottle each as much 80 ml. The parameter examined is alcohol test, test to boil, test reduktase and pH milk. The result of research indicate that best treatment is pasteurized of at temperature 70 ° C oldly 20 minute, able to maintain pH and time reduktase at longest depository until 12 day in refrigerator .